Umur Perusahaan Memoderasi Pengaruh Corporate Social Responsibility Disclosure dan Profitabilitas Pada Nilai Relatif Perusahaan - Dewi, Ni Putu Kiki Kusuma; Nyoman Badera, I Dewa (E-Jurnal Akuntansi, 2023)
The relative value of a company is an important aspect that shareholders need to pay attention to because it can reflect the financial performance of a company. The research aims to examine the influence of corporate social responsibility disclosure and profitability on the relative value of companies with company age as a moderating variable. Research was conducted on companies listed on the Indonesia Stock Exchange for the 2017-2021 period. In this research, a purposive sampling technique was used to obtain a sample of 117 observation data. The analysis technique in the research uses Moderated Regression Analysis with the help of SPSS software. The results of the research show that corporate social responsibility disclosure has a negative effect on the relative value of the company, profitability has a positive effect on the relative value of the company, company age weakens the effect of corporate social responsibility disclosure on the relative value of the company but company age does not moderate the effect of profitability on the relative value of the company. Keywords: Corporate Social Responsibility Disclosure; Profitability; Firm Age; Firm’s Relative Value